“I am going to Uni!” Working-class academic success, opportunity and conflict - Michael Ward (Masculinity, Labour and Neoliberalism: Working-Class Men in International Perspective, 2018)
Ward, M.R.M. (2017) “I am going to Uni!” Working-class academic success, opportunity and conflict, in Walker, C., and Roberts, S. (Ed.) Masculinity, Labour and Neoliberalism: Working-Class Men in International Perspective. Basingstoke, Palgrave MacMillan. 60-79.